The Influence of Language Diversity on Virtual Team Communication: Overcoming Barriers and Leveraging Benefits - Taylor, Danielle (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This qualitative, exploratory study analyzes the impact of language diversity on task-based and socio-emotional communication processes in multilingual virtual teams. The results highlight keys to effective communication for both completing team tasks and building relationships: 1) propose the use of a functional language for efficiency, but encourage supporting languages for building rapport, 2) use diverse communication channels to adapt to the context, message and interlocutors, but emphasize instant messaging for groups with high language diversity, and 3) identify language nodes as key facilitators of communication, understanding and rapport building within teams.